2007
DOI: 10.4219/jaa-2007-552
|View full text |Cite
|
Sign up to set email alerts
|

Project M3: Mentoring Mathematical Minds—A Research-Based Curriculum for Talented Elementary Students

Abstract: To date, there has been very little research-based mathematics curriculum for talented elementary students. Yet the gifted education and mathematics literature suggest support for curriculum that is both enriched and accelerated with a focus on developing conceptual understanding and mathematical thinking. Project M3: Mentoring Mathematical Minds is a 5-year Javits research grant project designed to create curriculum units with these essential elements for talented elementary students. These units combine exem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…The studies summarized in this section have demonstrated that enrichment pedagogy (Field, 2009;Reis et al, 2007Reis et al, , 2008, differentiation (Gentry & Owen, 1999;Tieso, 2002), acceleration (Colangelo et al, 2004), and curriculum enhancement and advanced lessons (Gavin et al, 2007;VanTassel-Baska et al, 2002) have resulted in higher achievement for gifted and talented learners as well as other students when they are applied to both gifted and other lower achieving students.…”
Section: Achievement Increases From Accelerated and Enriched Programsmentioning
confidence: 93%
See 4 more Smart Citations
“…The studies summarized in this section have demonstrated that enrichment pedagogy (Field, 2009;Reis et al, 2007Reis et al, , 2008, differentiation (Gentry & Owen, 1999;Tieso, 2002), acceleration (Colangelo et al, 2004), and curriculum enhancement and advanced lessons (Gavin et al, 2007;VanTassel-Baska et al, 2002) have resulted in higher achievement for gifted and talented learners as well as other students when they are applied to both gifted and other lower achieving students.…”
Section: Achievement Increases From Accelerated and Enriched Programsmentioning
confidence: 93%
“…Recent research has also documented positive effects regarding the use of gifted education programs and strategies when serving gifted and high ability students from diverse cultural groups (Gavin et al, 2007;Hébert & Reis, 1999;Little et al, 2007;Reis & Diaz, 1999;Reis et al, 2007Reis et al, , 2008 as well as when serving those with special education needs and those who have high ability but underachieve in school. Work in mathematics conducted by Gavin et al (2007) has been extended to culturally diverse children, as has been reading instruction differentiation and enrichment by Reis et al (2007Reis et al ( , 2008 as well as curriculum enhancement in social studies and language arts by VanTassel-Baska et al Underrepresentation of black and Latino students in gifted programs has been an ongoing problem in the field (Cunningham, Callahan, Plucker, Roberson, & Rapkin, 1998;Donovan & Cross, 2002;Frasier, 1991;Harris & Ford, 1991) and so these curriculum outreach efforts have been promising.…”
Section: Benefits Of Gifted Education Programs and Pedagogy For Divermentioning
confidence: 94%
See 3 more Smart Citations